PENINGKATAN KEMAMPUAN SPASIAL MELALUI PENERAPAN TEORI VAN HIELE TERINTEGRASI DENGAN MULTIMEDIA DENGAN MEMPERTIMBANGKAN GAYA BELAJAR SISWA - Budi Halomoan Siregar; Chrystin Yesica Siahaan; Hariyanti Hariyanti (JURNAL HANDAYANI PGSD FIP UNIMED, 2018)
Abstract : The Improvement of Students' Spatial Ability through Van Hiele???????????????????????????? ???????????????????????????????????????????? ???????????????????? ???????????????????????????????????????????? ???????????????????????? ???????????? ???????????????????????????????????????? ???????????????????????????????? ???????????????????????????? Thisstudy aims to identify: (1) an increase in the spatial ability of students taught withVan Hiele Theory that is integrated with multi-media compared to the application ofthe direct instruction method. (2) the interaction between Van Hiele theory which isintegrated with multimedia ???????????????? ???????????????????????????????????????? ???????????????????????????????????? ???????????????????????????? ???????? improvement of????????????????????????????????????????????????????????????????????????????????????????????????????. The population were all students of class VIII of junior highschool in two different schools consisting of 9 classes. Sample of 108 students aredivided into three group: visual learners, auditory learners and kinesthetic learners.The experimental group was subjected to Van Hiele theory which is integrated withmultimedia, while the control group was subjected to direct instruction model.Moreover, by using two-way ANOVA the results are as follows: (1) increasing of???????????????????????????????????????? ???????????????????????????????? ???????????????????????????????? ???????????????? ???????????????????? ???????????????????????????? ???????????? Van Hiele theory which is integratedwith multimedia better than direct instruction method. (2) There is an interactionbetween learning geometry based on Van Hiele theory integrated with multimediaand learning styles on increasing of students' spatial abilities. Furthermore, there is asignificant difference in spatial ability between students who have style visual,auditory, and kinesthetic learning styles.Keywords : Spatial Ability, Van Hiele Theory, Direct Instruction, MultimediaAbstrak : Peningkatan Kemampuan Spasial Melalui Penerapan Teori VanHiele Terintegrasi Dengan Multimedia Dengan Mempertimbangkan GayaBelajar Siswa. Penelitian ini bertujuan untuk mengidentifikasi: (1) peningkatankemampuan spasial siswa yang diajarkan dengan Teori Van Hiele yang terintegrasidengan multi-media dibandingkan dengan penerapan metode pengajaran langsung.(2) interaksi antara teori Van Hiele yang terintegrasi dengan multimedia dan gayabelajar siswa pada peningkatan kemampuan spasial siswa. Populasinya adalahsemua siswa kelas VIII SMP di dua sekolah berbeda yang terdiri dari 9 kelas.Sampel dari 108 siswa dibagi menjadi tiga kelompok: pelajar visual, pelajar auditoridan pelajar kinestetik. Kelompok eksperimen menjadi sasaran teori Van Hiele yangterintegrasi dengan multimedia, sedangkan kelompok kontrol dikenakan modelpengajaran langsung. Selain itu, dengan menggunakan ANOVA dua arah, hasilnyaadalah sebagai berikut: (1) peningkatan kemampuan spasial siswa yang diajarkanoleh teori Van Hiele yang terintegrasi dengan multimedia lebih baik daripadametode instruksi langsung. (2) Ada interaksi antara geometri pembelajaranberdasarkan teori Van Hiele yang terintegrasi dengan multimedia dan gaya belajarpada peningkatan kemampuan spasial siswa. Selanjutnya, ada perbedaan yangsignifikan dalam kemampuan spasial antara siswa yang memiliki gaya belajar visual,auditori, dan kinestetik.Kata kunci: Kemampuan Spasial, Teori Van Hiele, Instruksi Langsung, Multimedia